Expertise in professional software design: a process study. - Sonnentag, Sabine (Journal of Applied Psychology, 1998)
Forty professional software designers participated in a study in which they worked on a software design task and reported strategies for accomplishing that task. High performers were identified by a peer-nomination method and performance on a design. Verbal protocol analysis based on a comparison of 12 high and 12 moderate performers indicated that high performers structured their design process by local planning and showed more feedback processing, whereas moderate performers were more engaged in analyzing requirements and verbalizing task-irrelevant cognitions. High performers more often described problem comprehension and cooperation with colleagues as useful strategies. High and moderate performers did not differ with respect to length of experience. None of the differences between the two performance groups could be explained by length of experience. Reprinted by permission of the publisher.